Differential Expression of MMP2 and TIMP2 in Peripheral Blood Mononuclear Cells After Roux-en-Y Gastric Bypass - Nonino, Carla Barbosa; Noronha, Natália Yumi; de Araújo Ferreira-Julio, Maysa; Moriguchi Watanabe, Lígia; Cassia, Karen Francislaine; Ferreira Nicoletti, Carolina; Rossi Welendorf, Caroline; Salgado Junior, Wilson; Rossi Silva Souza, Dorotéia; Augusta de Souza Pinhel, Marcela (Frontiers in Nutrition, 2021)
Matrix metalloproteinases (MMP) and their endogenous inhibitor, the tissue inhibitor of metalloproteinases (TIMP), are expressed in many different cell types and play an important role in physiologic and pathological degradation of extracellular matrix (ECM). Starting from these observations and considering the activation state of peripheral blood mononuclear cells (PBMCs) in obesity, we investigated the gene expression of metalloproteinases before and after Roux-en-Y gastric bypass (RYBG). The study was performed in the Ribeirão Preto Medical School University Hospital. Seventy-three women were divided into a study group (SG), composed of 53 individuals with severe obesity before and after 6 months of RYGB, and a control group (CG), composed of 20 normal-weight individuals. Anthropometric and body composition data were collected, and peripheral blood for ribonucleic acid (RNA) extraction. The biological samples were submitted to a quantitative real-time polymerase chain reaction to evaluate the expression of MMP2 and TIMP2 genes. Alterations in weight loss, body mass index (BMI), and fat mass (FM) were observed after 6 months of RYGB (p < 0.05). A reduction of gene expression of TIMP2 was observed after 6 months of RYGB, contributing positively to the weight loss (R2 = 0.33 p = 0.04). The enrichment analyses highlighted the interaction between TIMP2 and MMP2 genes and the molecular pathways involving the ECM remodeling in the obesity condition. RYGB contributes significantly to weight loss, improved BMI, reduced FM, and reduced TIMP2 expression in PBMCs, which might contribute to the ECM remodeling in the obesity and could be useful as a circulating biomarker.